2018
DOI: 10.1159/000485793
|View full text |Cite
|
Sign up to set email alerts
|

Use of Vitamin K Antagonists and Brain Morphological Changes in Older Adults: An Exposed/Unexposed Voxel-Based Morphometric Study

Abstract: Background: Vitamin K antagonists (VKAs) are commonly used for their role in haemostasis by interfering with the vitamin K cycle. Since vitamin K also participates in brain physiology, this voxel-based morphometric study aimed to determine whether the duration of exposure to VKAs correlated with focal brain volume reduction in older adults. Methods: In this exposed/unexposed (1: 2) study nested within the GAIT (Gait and Alzheimer Interactions Tracking) cohort, 18 participants exposed to VKA (mean age 75 ± 5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Brangier et al analyzed the brain volume, using 3 or 1.5 Tesla MRI, of 54 subjects (18 under VKAs treatment and 36 matched controls) and found a significant inverse correlation between the duration of drug exposure and gray/white matter volume in the right frontal inferior operculum, right precuneus, and left middle frontal gyrus (71). The same author found an important decline in executive functions (assessed with frontal assessment battery) among geriatric patients treated with VKAs over at 24 months follow up.…”
Section: Vitamin K and Cognitive Declinementioning
confidence: 99%
“…Brangier et al analyzed the brain volume, using 3 or 1.5 Tesla MRI, of 54 subjects (18 under VKAs treatment and 36 matched controls) and found a significant inverse correlation between the duration of drug exposure and gray/white matter volume in the right frontal inferior operculum, right precuneus, and left middle frontal gyrus (71). The same author found an important decline in executive functions (assessed with frontal assessment battery) among geriatric patients treated with VKAs over at 24 months follow up.…”
Section: Vitamin K and Cognitive Declinementioning
confidence: 99%
“…Also in older adults, smaller whole-brain volume has been reported among those taking VKA regulary 9 compared to those taking no anticoagulant [7]. Specifically, the exposure to VKA correlated in another study with focal atrophies within the frontal lobes [8]. All these previous studies have yet addressed the brain changes only in terms of cerebral atrophy.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, the use of VKA in animals has been associated with cognitive impairment and a dysregulation of the synthesis of sphingolipids, a constituent of the myelin sheath and neuronal membrane [6], and a reduction of the biological activation of the vitamin K-dependent proteins involved in neuronal physiology and survival [5]. Such changes may account for the onset of pathological morphological brain changes in VKA users [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Again, no significant association with MMSE scores was seen [ 123 ]. The same research group performed another study of brain morphological changes in patients taking VKAs and observed focal atrophies in older adults exposed to VKAs (18 community-dwellers), compared to 36 matched controls [ 124 ]. Annweiler et al further showed that fluindione treatment specifically caused more frequent cognitive impairment among 267 geriatric patients (56.9% female; mean age 83.4 ± 8.1 years) [ 125 ].…”
Section: Potential Therapeutic Benefitsmentioning
confidence: 99%